The Influence of Principal’s Leadership and Teacher’s Performance on Educational Quality - Ernawati, Farizah; Ahmad, Syarwani; Tahrun, Tahrun (Journal of Social Work and Science Education, 2023)
This study was conducted to provide a comprehensive description of the principal’s leadership and teacher’s performance on the quality of education. The method used in this study is a quantitative. The results obtained that partially there is an influence of the principal’s leadership on the quality of education; partially there is an influence of teacher’s performance on the quality of education; Likewise, simultaneously there is the influence of the principal’s leadership and teacher’s performance on the quality of education in SMA Negeri in South OKU Rayon 1.